2015
DOI: 10.1515/eces-2015-0042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foliar Application of Titanium on Seed Yield in Timothy (Phleum pratense L.)

Abstract: Abstract:Titanium is one of a plant biostimulators. It stimulates life processes, growth and development, as well as affects physiological and biochemical pathways, often increasing biomass production and enhancing yield. An open field experiment was conducted in the years 2011-2013 in Polanowice, Poland to investigate the effects of titanium foliar fertilization on the growth of timothy grass (Phleum pratense L.). This single-factor, randomized block design study was performed in four replicates on research p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Studies done by Radkowski et al, (2015) demonstrated that an increase in the Phleum pratense L. yield after Tytanit application was due to its influence on plant morphological parameters. The authors found that the highest dose (0.8 dm 3 ha −1 ) contributed to an increase in the length of stems, florescence, and leaf blades of this species, leading to 19.5% yield growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies done by Radkowski et al, (2015) demonstrated that an increase in the Phleum pratense L. yield after Tytanit application was due to its influence on plant morphological parameters. The authors found that the highest dose (0.8 dm 3 ha −1 ) contributed to an increase in the length of stems, florescence, and leaf blades of this species, leading to 19.5% yield growth.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, new effective methods and environmentally friendly solutions are needed to improve the health and quality of plants ( Ilieva and Vasileva, 2013 , Janas et al, 2013 , Serrano et al, 2004 , Szparaga et al, 2018 , Kocira et al, 2019 , Vasileva et al, 2017 ). One of such biostimulants is Tytanit ( Godlewska and Ciepiela, 2018 , Malinowska and Kalembasa, 2012 , Radkowski and Radkowska, 2013 , Radkowski et al, 2015 , Wadas and Kalinowski, 2017a ), the active ingredient of which is titanium (Ti). This chemical element is a micronutrient having a positive effect on plant biochemistry, supporting processes leading to an acceleration of plant growth and to an increase in the production of biomass ( Kužel et al, 2003 , Lyu et al, 2017 , Radkowski and Radkowska, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Janas [36] showed that in the cultivation of onion for seed production, treated plants demonstrated a higher seed yield and a better quality and health status after foliar spraying with that compound compared to nontreated plants. Similarly, Radkowski et al [37] obtained a higher yield, thousand-grain weight, and germination capacity of timothy seeds due to foliar application of the titanium organic complex.…”
Section: Introductionmentioning
confidence: 89%
“…Titanium (Ti) is one of a plant biostimulators and presence of Ti in plant tissues improves plant enzyme activities, particularly those involved in the photosynthesis redox processes( as nitrate reductase, lipoxygenase, peroxidase, fructose-1,6-bisphosphatase). Plant supplementation with Ti stimulates their chlorophyll content, growth, pollination, fruit and seed formation (Radkowski et al, 2015).…”
Section: D-yield and Its Componentsmentioning
confidence: 99%